Effective delivery of the anti-mycobacterial peptide NZX in mesoporous silica nanoparticles. - Erik Tenland; Alexander Pochert; Nitya Krishnan; Komal Umashankar Rao; Sadaf Kalsum; Katharina Braun; Izabela Glegola-Madejska; Maria Lerm; Brian D Robertson; Mika Lindén; Gabriela Godaly (PLoS ONE, 2019)
Background Intracellular delivery of antimicrobial agents by nanoparticles, such as mesoporous silica particles (MSPs), offers an interesting strategy to treat intracellular infections. In tuberculosis (TB), Mycobacterium tuberculosis avoids components of the immune system by residing primarily inside alveolar macrophages, which are the desired target for TB therapy. Methods and findings We have previously identified a peptide, called NZX, capable of inhibiting both clinical and multi-drug resistant strains of M. tuberculosis at therapeutic concentrations. In this study we analysed the potential of MSPs containing NZX for the treatment of tuberculosis. The MSPs released functional NZX gradually into simulated lung fluid and the peptide filled MSPs were easily taken up by primary macrophages. In an intracellular infection model, the peptide containing particles showed increased mycobacterial killing compared to free peptide. The therapeutic potential of peptide containing MSPs was investigated in a murine infection model, showing that MSPs preserved the effect to eliminate M. tuberculosis in vivo. Conclusions In this study we found that loading the antimicrobial peptide NZX into MSPs increased the inhibition of intracellular mycobacteria in primary macrophages and preserved the ability to eliminate M. tuberculosis in vivo in a murine model. Our studies provide evidence for the feasibility of using MSPs for treatment of tuberculosis.